Exact optical solitons of the perturbed nonlinear Schrodinger-Hirota equation with Kerr law nonlinearity in nonlinear fiber optics - Houwe, Alphonse; Abbagari, Souleymanou; Betchewe, Gambo; İnç, Mustafa; Doka, Serge Y.; Crepin, Kofane Timoleon; Almohsen, Bandar (De Gruyter Poland Sp Z O O, 2020)
This article studies dark, bright, trigonometric and rational optical soliton solutions to the perturbed nonlinear Schrodinger-Hirota equation (PNLSHE). Hence, we have examined two cases: first, restrictions have been done to the third-order (TOD) (gamma) as constraint relation, and the coupling coefficients (sigma) is obtained as well as the velocity of the soliton by adopting the traveling wave hypothesis. Second, the TOD and the coupling coefficients are non-zero value, sending back to the PNLSHE, which has been studied in refs. [4,10,16] recently. By employing two relevant integration technics such as the auxiliary equation and the modified auxiliary equation method, miscellaneous optical solitary wave is obtianed, which is in agreement with the outcomes collected by the previous studies [4,16]. These results help in obtaining nonlinear optical fibers in the future.
Keywords: optical solitons; perturbed nonlinear Schrodinger-Hirota equation